Analysis Of Nursing Practices For STEMI Patients With The Innovational Intervention Of A Combination Of Swedish Massage With Olive Oil And Warm Water - Nur Sausan Fauziah; Zulmah Astuti; Ulfatul Muflihah; Dwi Widyastuti (International Journal of Public Health Excellence (IJPHE), 2026)
ST-Elevation Myocardial Infarction (STEMI) is part of Acute Coronary Syndrome (ACS), a cardiovascular condition in which a coronary artery is completely occluded, preventing oxygen from reaching the heart muscle. This study aimed to determine the effect of Swedish massage therapy combined with warm water on hemodynamic stability. This study employed a case study design comparing an intervention patient and a control patient diagnosed with STEMI who had unstable hemodynamic status in the ICCU. After the implementation of Swedish massage and warm water therapy in the intervention patient for three consecutive days, the patient’s hemodynamic parameters such as blood pressure, heart rate, mean arterial pressure, and respiratory rate remained within stable limits, showing no significant increases or decreases. This outcome differed from the control patient, who received only pharmacological therapy. The analysis deminstated a difference in hemodynamic outcomes between patients who received the combined intervention and those in the control group.